Evaluating the reality of unity and diversity in print ad design systems (Journal of the College of Basic Education, 2022)
Design systems are the basis for achieving unity and diversity in showing the design idea of ​​the printed advertisement.It gives an effect that the designer achieves through the final verification of the idea, which is the basis on which the research problem was identified by revealing the fact that unity and diversity are a prerequisite for building an effective and vital design system in the overall body of the printed advertisement.In order to reach the desired results, the goal of the research was established, which is: Evaluating the reality of unity and diversity in the systems of print advertising.